One-Pot Preparation of Stable Organoboronate Reagents for the Functionalization of Unsaturated Four- and Five-Membered Carbo- and Heterocycles - Baumann, Andreas N.; Eisold, Michael; Music, Arif; Didier, Dorian (Synthesis, 2018)
Combining a facile preparation of organoboronates with their remarkable stability and functional group tolerance allows for the straightforward synthesis of four- and five-membered carbo- and heterocycles. While most strategies rely on the ex situ preparation of boronic acids as isolated intermediates, we demonstrate that in situ transmetalation of sensitive organometallics with boron alkoxides can lead to great stabilization of such species at room temperature. A considerable extension of the library of unsaturated strained structures is achieved through these sequences, expanding the potential applicability of such unusual building blocks.
Keywords: cyclobutenes; cyclopentenes; azetines; organoboronates; one-pot sequences